2019
DOI: 10.3389/fpsyg.2018.02692
|View full text |Cite|
|
Sign up to set email alerts
|

Eating Disorder Symptoms and Proneness in Gay Men, Lesbian Women, and Transgender and Gender Non-conforming Adults: Comparative Levels and a Proposed Mediational Model

Abstract: In this study we sought to compare eating disorder attitudes and behaviors, and proneness to an eating disorder (“ED proneness”), between gay men, lesbian women, and transgender and gender non-conforming (TGNC) adults. A further aim was to identify and compare risk and protective factors, and examine a mediational model based on the interpersonal theory of eating disorders (IPT-ED), whereby the association between interpersonal factors and ED proneness would be mediated by psychological constructs pertaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 61 publications
7
65
0
Order By: Relevance
“…Similarly, transgender women previously reported higher scores on the Shape Concern subscale than presumed cisgender women [20]. Shape concerns in genderexpansive individuals may be linked to gender dysphoria and body dissatisfaction when one's body shape is discrepant from one's gender identity [18,37,38]. It may be especially challenging for gender-expansive individuals to attain certain shape ideals when certain anatomic structures cannot be altered medically or surgically [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, transgender women previously reported higher scores on the Shape Concern subscale than presumed cisgender women [20]. Shape concerns in genderexpansive individuals may be linked to gender dysphoria and body dissatisfaction when one's body shape is discrepant from one's gender identity [18,37,38]. It may be especially challenging for gender-expansive individuals to attain certain shape ideals when certain anatomic structures cannot be altered medically or surgically [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al [17] have described invalidation ("the refusal to accept someone's identity as 'real' or 'true'") as a unique form of minority stress that impacts genderexpansive individuals and is a contributing factor to significant psychological distress. Bell et al [18] found that perceived stigma was indirectly associated with eating disorder proneness that was mediated by self-compassion among transgender and gender-nonconforming adults.…”
Section: Introductionmentioning
confidence: 99%
“…Transgender individuals are also at higher risk of EDs due to general body dissatisfaction and desire to affirm gender through body shape (Jones et al, 2018;Testa, Rider, Haug, & Balsam, 2017). Underlining the intersectionality of stigma processes, the persistent sexual stigma experienced by LGBT communities can amplify ED proneness (Bell, Rieger, & Hirsch, 2019). However, no studies in this review investigated how the experience of ED stigma interacted with LGBT identities.…”
Section: Gaps and Weakness In The Literaturementioning
confidence: 95%
“…Researchers of ED in sexual and gender minorities stress the relevance of stigmatization and its psychological consequences ( Bell et al, 2019 ). Scholars have established the fact that minority stress leads to psychological strain ( Meyer, 2003 ), but in terms of ED, it is important to understand how minority stress influences a person’s relationship with their body ( Bosley, 2011 ).…”
Section: Theoretical Implications For Diverse Genders and Sexual Minomentioning
confidence: 99%
“…As Testa et al (2017) demonstrated, the effect of gender confirming interventions on body satisfaction is mediated by reduced non-affirmating social experiences (e.g., being referred to with incorrect pronouns). Various studies have highlighted the general importance of social acceptance versus discrimination for ED pathology in transgender and non-binary persons ( Watson et al, 2017 ; Bell et al, 2019 ). Goldhammer et al (2019) have outlined ways to address minority stress issues in interventions.…”
Section: Theoretical Implications For Diverse Genders and Sexual Minomentioning
confidence: 99%